Procura de Nova Física em Anéis de Colisão Hadrônicos - Alves, Alexandre [UNESP] (2004)
We present the search for new physics at subatomic scales at hadron colliders in two important phenomenological scenarios -- the spontaneous symmetry breaking sector and the R-parity violating extension of the MSSM. In the first part of this thesis, we show that extensions of the Standard Model and the MSSM, which embody a complex spontaneous symmetry breaking sector containing an arbitrary number of 'SU(2) IND. L' escalar doublets and singlets, can be easily studied at the LHC in the weak boson fusion process with the subsequent decay to leptons. About 10 'fb POT. -1' a 50 'fb POT. -1' of integrated luminosity will be necessary in order to get a 5'sigma' level signal. We also show that the weak bosons' transverse mass distributions can be used to distinguish the continuum model from the Standard Model case, however, the gluon fusion process in the same decay channel may be more promising in this regard. In the second part of the thesis, we compute the full NLO SUSY-QCD corrections to the stop/sbottom lepton associated production at the Tevatron and at the LHC in the MSSM framework extended by R-parity breaking couplings. The NLO correc- tions increase the total cross sections up to 70%(50%) at the Tevatron(LHC) and reduce the theoretical uncertanties related to the choice of the renormalization and factorization scales. Decoupling the heavy SUSY spectrum, we show that the search reach of the Tevatron and the LHC for scalar leptoquarks, which couple to up and down quarks and decay exclusively to quarks and leptons, increases using the NLO rates. For the Tevatron, leptoquarks of masses up to 310 GeV can be excluded to 95% C.L., while for the LHC, leptoquarks of masses up to 3.1 TeV can be excluded at the same statistical level